POSTDIGITAL RECYCLING IN THE WORK OF ALMUDENA LOBERA, MARIO SANTAMARÍA Y ROMÁN TORRE (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2024)
This article is the result of research on postdigital recycling in the context of contemporary artistic practices and aims to highlight the applicability of this term and identify some of its compositional strategies in relation to the works of three contemporary Spanish artists (Almudena Lobera, Mario Santamaría, Roman Torre). In the first section, the characteristics of postdigital recycling in contemporary artistic practices will be addressed, to later deepen the definition of the strategies of transcodification, technological reappropriation and artistic hacktivisim, and, finally, some works of these three Spanish artists will be analysed, exploring how they question the public through the construction of objects, installations and mechanisms that make visible and subvert our habits of technological consumption. We will observe how they make use of the fluid interpenetration of the different exhibition spaces, both analogue and digital, as well as the exploration of their interstices, creating hybrid (phygital) objects that conflict with the traditional notions associated with each medium and propose to the public new interfaces that reveal what we have made invisible in our hybridization with the machine.
Keywords: Postdigital Recycling; transcodification; technological reappropriation; artistic hacktivism; phygital